2019
DOI: 10.1039/c8sc05735d
|View full text |Cite
|
Sign up to set email alerts
|

Controlling nanoemulsion surface chemistry with poly(2-oxazoline) amphiphiles

Abstract: Poly(2-oxazoline) surfactants allow for the stabilization and functionalization of hydrocarbon- and perfluorocarbon-in-water nanoemulsions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 129 publications
1
43
0
Order By: Relevance
“…At scheduled time points (0. 5,1,2,3,4,5,6,7,8,9,10,11,12,24,36,48,60,72,84, and 96 h), release medium (1.0 mL) were taken out, and fresh medium (1.0 mL) were added. The amount of drug released was determined by multi-mark detection system (En Vision, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At scheduled time points (0. 5,1,2,3,4,5,6,7,8,9,10,11,12,24,36,48,60,72,84, and 96 h), release medium (1.0 mL) were taken out, and fresh medium (1.0 mL) were added. The amount of drug released was determined by multi-mark detection system (En Vision, USA).…”
Section: Methodsmentioning
confidence: 99%
“…[9] During the physical circulation, the neutrally or negatively charged NPs could stay stable, and greatly decrease the interaction with plasma proteins electrostatic force or the cytotoxicity to normal cells. [10,11] But in the tumor, the stable NPs could change into positively charged NPs and enhance the affinity with negatively charged tumor cells to increase cellular uptake. Hu et al developed a new drug delivery system by adding chitosan to silk protein in which the designed SSC@NPs are stable with a negative surface charge at neutral environment and could trigger a negative-to-positive conversion under acidic tumor condition.…”
Section: Introductionmentioning
confidence: 99%
“…[b] Characterized as previously reported. [18] Angewandte Chemie Communications PFC droplets to GSH on the macroscale using fluorescein to track the aqueous phase and a fluorous-soluble rhodamine dye (8, Figure 3 B) [34] to track the fluorous phase (Figure 3 C, i). Surfactants 5 and 6 were added to each layer (2.8 wt %), and emulsified (Figure 3 C, ii).…”
mentioning
confidence: 99%
“…We have successfully encapsulated small molecule fluorophores and therapeutics within PFC nanoemulsions through covalent attachment of fluorous tags. [14,[16][17][18][19] Recently, Medina and co-workers extended the payloads capable of being delivered with PFC nanoemulsions to include proteins by creating a "fluorous mask" around GFP with non-covalent fluorinated anionic tags. [20] GFP was then delivered in cells using ultrasound-induced cavitation.…”
mentioning
confidence: 99%
“…We have previously developed poly(2-oxazoline) (POx) block copolymer surfactants capable of stabilizing oil-inwater nanoemulsions. [18,19] These amphiphiles form sub-200 nm droplets through emulsification involving either PFCs or olive oil as the emulsion core. We found that a poly(2-methyl-2-oxazoline)-b-poly(2-nonyl-2-oxazoline) (P(MeOx) 30 -b-P(NonOx) 12 , 6, Figure 2 A) diblock copolymer was optimal for emulsions of < 200 nm in size with stability over 60 days.…”
mentioning
confidence: 99%